THE INFLUENCE OF REGIONAL INCOME, GENERAL ALLOCATION FUNDS AND REVENUE SHARING FUNDS ON THE ALLOCATION OF CAPITAL EXPENDITURES WITH ECONOMIC GROWTH AS A MODERATING VARIABLE IN GOVERNMENTS EAST JAVA PROVINCE 2019-2022 - Prayitno, Budi; Wany, Eva; Abidin, Khoirul (SENTRI: Jurnal Riset Ilmiah, 2024)
This research aims to test and analyze the influence of Regional  Income, General Allocation Funds, and Profit Sharing Funds on Capital Expenditures as well as the influence of Regional  Income, General Allocation Funds, and Profit Sharing Funds with moderating economic growth on Capital Expenditures. This research was conducted at the Regency/City government in East Java Province. The sampling technique used was saturated sampling , and there were 36 districts/cities in East Java that were the sample for this research. This research uses the APBD Realization Report and GRDP Table for the 2019-2022 period as samples. The analytical method used to test the hypothesis in the research is Moderated Regression Analysis (MRA). The results of this research show that Regional  Income, General Allocation Funds have an effect on capital expenditure in the Regency/City of East Java Province, but the Profit Sharing Fund variable has no effect on capital expenditure. The moderating variable (economic growth) is able to moderate the Profit Sharing Fund variable, but is not able to moderate the Regional  Income and General Allocation Fund variables on capital expenditure.